Interactive Role of Sand and Geomaterial Geometries on Microscale Interface Shear Response - Ari, Abdulmuttalip; Akbulut, Suat (ASCE-AMER SOC CIVIL ENGINEERS, 2025)
Shear response of interfaces evolves as a result of the interactive roles of sand and geomaterial geometries. However, studies have addressed the effects of geometric properties on the response individually. This study investigates the coupled effects of sand and geomaterial geometries on microscale response of interfaces using particle shape and gradation, roughness form, and height parameters. Interface shear analyses are performed using the discrete-element numerical method. The model parameters are calibrated using a custom-made transparent interface shear box device. The results show that the effects of particle shape and roughness form on the shear strength amplify with increasing uniformity coefficient. The influence of roughness form vanishes with increasing roughness height. As the particle irregularity and uniformity coefficient increase, the coordination number and anisotropy coefficient spread over a wider range, and the role of the roughness form becomes more important. Particle displacement and rotation reveal the traces of interlocking and trapping mechanisms depending on the material geometry. The average rotation of particles in shear band increases with increasing particle regularity and follows similar trends for different particle gradations. In addition, an optimum trend in the rotation level occurs as the roughness height changes depending on the roughness form. Overall, this study reveals that the optimum design of interfaces between sand and geomaterials such as geosynthetics, concrete, and steel can be achieved by considering the interplay role of material geometries.
Keywords: Material geometry; Sand; Geomaterial; Interactive role; Interface response; Discrete-element method; PARTICLE-SHAPE; BEHAVIOR; SOIL; DEM; ASSEMBLIES; STRENGTH; FRICTION; IMAGE; STATE; RATIO; Engineering